Contribution of Social Identity, Stereotypes and Prejudice on Intention of Social Conflict - Hadi Suyono; Yuni Nirwanasari (Journal An-Nafs: Kajian Penelitian Psikologi, 2022)
The intention to accurately predict the performance of social conflict behavior is influenced by stereotypes, social identity, and prejudice. Based on the dynamics of the relationship, this research aims to find the relationship between stereotypes, social identity, and prejudice with the intention of doing social conflict. Based on the analysis result, intentions are useful for preventing social conflict. This study used purposive sampling with the participants of 150 students in the 10th grade of State Senior High School (SMAN) 1 Belitang in East Oku Regency, South Sumatra Province. The research data were collected using a social conflict intention scale with a total of 21 items with the item determinant (rit) ranging from 0.274-0.777, a stereotypes scale with a total of 24 items ranging from 0.291 to 0.841, a social identity scale with a total of 21 items ranging from 0.290 to 0.897, and a prejudice scale with a total of 21 items ranging from 0.400. -0.796. The results of data analysis using multiple linear regression showed that the correlation coefficient of R is 0.269 with the p = 0.000 (p <0.05), which showed a significant positive relationship between stereotypes, social identity, and prejudice with the intention of social conflict. Based on the research results, the intention of a social conflict occurs because of stereotypes in which people give negative attributes or traits to other parties, social identity that causes bias to judge other groups, and prejudice that causes hostility to members of other groups. These findings can be used for conflict prevention by minimizing the intention of social conflict by changing stereotypes into positive judgment, knowing that social identity does not affect the objective judgment of other groups, and reducing prejudice so that a peaceful situation can be realized.